A novel Vision Zero leadership training model to support collaboration and strategic action planning - Naumann, Rebecca B.; LaJeunesse, Seth; Keefe, Elyse; Heiny, Stephen; Hassmiller Lich, Kristen; Jones, Ki’yonna; Evenson, Kelly R. (Frontiers in Future Transportation, 2023)
While collaboration and cooperation are regarded as foundational to Vision Zero (VZ) and Safe Systems initiatives, there is little guidance on structuring VZ collaboration, conducting collaborative goal setting, and aligning tangible action across organizations. As part of a larger VZ mutual learning model, we developed a VZ Leadership Team Institute to support communities in collaborative VZ strategic planning and goal setting. The purpose of this paper is to describe the development and evaluation of the Institute, which can serve as a foundation for other initiatives seeking to move VZ planning and implementation forward in a collaborative, systems-aware manner. In June 2021, eight multi-disciplinary teams of 3-6 persons each (n=42 participants) attended the Institute, representing leaders from communities of various sizes. Surveys were administered pre, immediately post, and six months following the Institute. We measured confidence in a range of skills (on a 5-point scale, 1: not confident to 5: very confident). The largest increases in confidence from pre- to immediately post-Institute were for collaboratively drafting objectives and actions for VZ goals (pre-mean:2.6, SD:0.9 to post-mean:3.8, SD:0.9); incorporating equity into goals (pre-mean:2.8, SD:1.0 to post-mean:3.9, SD:0.8); and knowing how to keep VZ planning and implementation efforts on track (pre-mean:2.6, SD:1.0 to post-mean:3.7, SD:0.7). For all measures, average confidence in skills decreased from immediately post-Institute to six months post-Institute, but remained greater than average scores pre-Institute. Surveys also measured coalition collaboration pre-Institute and six months post-Institute (on a 4-point scale, 1: strongly disagree to 4: strongly agree). Several measures maintained high agreement across time, and mean agreement increased for reporting that the future direction of the coalition was clearly communicated to everyone (pre-mean:2.6, SD:0.8; six months post-mean:3.1, SD:0.4) and decreased for feeling like the coalition had adequate staffing (pre-mean:3.0, SD:0.6; six months post-mean:2.3, SD:0.5). The Institute utilized innovative content, tools, and examples to support VZ coalitions’ collaborative and systems-aware planning and implementation processes. As communities work toward zero transportation deaths and serious injuries, providing effective support models to aid multidisciplinary planning and action around a Safe Systems approach will be important to accelerate progress toward a safer transportation system.